Extraction, Antioxidant Capacity, 5-Lipoxygenase Inhibition, and Phytochemical Composition of Propolis from Eastern Canada - Mariama Sambou; Jacques Jean-François; Fanta J. Ndongou Moutombi; Jérémie A. Doiron; Mathieu P.A. Hébert; Andrew P. Joy; Ngoc-Nu Mai-Thi; David A. Barnett; Marc E. Surette; Luc H. Boudreau; Mohamed Touaibia (Molecules, 2020)
Soxhlet (SE), microwave-assisted (MAE) and ultrasound-assisted (UAE) extraction were compared using ten extraction solvents for their efficiency to extract phenolic and flavonoid antioxidants from Eastern Canada propolis. Extracts were compared for total phenolic (TPC) and total flavonoid (TFC) content, and radical scavenging activities. Anti-inflammatory activity through inhibition of 5-lipoxygenase (5-LO) products biosynthesis in HEK293 cells was also evaluated. The results showed that SE extracts using polar solvents had the highest TPC and TFC. Extracts obtained with ethanol, methanol and acetone were effective free radical scavengers, and showed 5-LO inhibition similar to zileuton. UAE was an effective extraction method since the extracts obtained were comparable to those using SE and the MAE while being done at room temperature. With UAE, extracts of less polar solvents showed similar free radical scavenging and 5-LO inhibition to extracts of much more polar solvents such as methanol or ethanol. Reversed-phase liquid chromatography tandem mass spectrometry confirmed the presence of 21 natural compounds in the propolis extracts based on the comparison of intact mass, chromatographic retention time and fragmentation patterns derived from commercial analytical standards. The current study is the first of its kind to concurrently investigate solvent polarity as well as extraction techniques of propolis.